DEVELOPMENT OF A WEB-BASED INFORMATION SYSTEM FOR MONITORING CONSTRUCTION PROJECTS TO ENHANCE PROJECT CONTROL - Prionggo Hendradi; Angga Agista (Jurnal Ilmiah Universitas Satya Negara Indonesia, 2026)
The implementation of construction projects requires an effective monitoring system to ensure alignment between project planning and actual execution in terms of schedule, cost, and work progress. However, in many construction companies, project monitoring is still conducted manually, which may lead to information delays, data inaccuracies, and reduced effectiveness in decision-making. This study aims to develop and implement a web-based construction project monitoring information system to support project control at PT. Edco Medco. The system is developed using a software engineering approach with the waterfall method and utilizes PHP-based web technology with MySQL as the database. The proposed system provides integrated project information, including project data, schedules, work progress, documentation, and project reports in real time. Functional testing results indicate that the system operates in accordance with user requirements and enhances the effectiveness of project monitoring compared to conventional manual methods. The implementation of this system is expected to improve transparency, accuracy of project control, and efficiency in construction project management within the organization.